Optimasi Administrasi Turnitin Digital Berbasis Portal Web dan Verifikasi QR-Code PGSD FKIP Universitas Lampung - Ulfa Nurfitria Ardilla; Fadhilah Khairani; Agung Dian Putra; Dayu Rika Perdana (Jurnal Dremi (Demi Pengabdi Masyarakat), 2026)
The plagiarism-check administration service for undergraduate theses at the Elementary School Teacher Education Department (PGSD), FKIP Universitas Lampung, was previously managed manually through WhatsApp, with a waiting time of one to three working days, no status tracking, and limited document security. This community service program aimed to develop and implement a web-based Digital Turnitin Administration Portal as an efficient, transparent, and secure service transformation. The method consisted of needs analysis, system design, portal development, testing, academic coordination, user socialization, and monitoring and evaluation. The portal was developed using Laravel 10 and MySQL 8.0 and equipped with unique tokens and QR-Codem enabled certificates verifiable in real time. During the implementation period, the portal processed 79 documents, issued 72 certificates (91.13%), and reached 533 students through socialization. A user satisfaction survey of 50 respondents yielded an average score of 4.61 out of 5.00. The transformation reduced service time to less than 24 hours, eased administrative workload, and strengthened academic document integrity.